Community participation in the development of the tourism area of Segunung indigenous village in Carangwulung village, Wonosalam district, Jombang regency - Rahmiyati, Nekky; Andayani, Sri; Indartuti, Endang (International research journal of management, IT and social sciences, 2021)
Wonosalam, a sub-district in Jombang Regency, East Java Province, is located at the foot and slopes of Mount Anjasmoro with an average height of 500-600 meters above sea level. Wonosalam District is located 35 km southeast of Jombang District. In addition, the Wonosalam area also has great tourism potential, especially agro-tourism, because the majority of the population's livelihood is farmers. This program was initiated because of the need to build villages into Tourism Villages according to the direction of the President in 2017 for the movement to develop tourist villages by combining villages with tourism to build a people's economy and create national resilience through independent villages. The results showed that: first, community support was realized in the form of community participation in the planning process of tourism development. Second, participation in planning. Third, participation in implementation is participation in decision-making. Fifth, participation in receiving benefits and participation in evaluating. Sixth, as well as participation in the subsequent development.